#FeesMustFall Protests in South Africa: A Critical Realist Analysis of Selected Newspaper Articles (Journal of Student Affairs in Africa, 2021)
Using Critical Realism (CR), this article looks at articles from selected South African newspapers which reported on the #FeesMustFall protests. The study established that, arising from the protests, was a culture characteried by tensions and distrust among stakeholders such as students, university management and the government. This, the article argues, was a result of how each of these stakeholdersperceived, and went on to exercise, their agency in an attempt to resolve the conflict arising from the protests. To avert a recurrence of negative consequences of student protests such as the destruction of property and development of toxic and adversarial relationships amongst different stakeholders, the article recommends collaborative approaches to conflict resolution in South African higher education. These approaches need to be framed differently from those in which some stakeholders seek to use theiragency to achieve outright victory over other stakeholders - a recurring mode of engagement during the #FeesMustFall protests.
Keywords: agency; critical realism; culture; #FeesMustFall; higher education; protests; student movements; student politics